Alpha lipoic acid combined with epalrestat: a therapeutic option for patients with diabetic peripheral neuropathy - Wang XT; Lin HX; Xu S; Jin YL; Zhang R (Dove Medical Press, 2018)
Xiaotong Wang,1,* Haixiong Lin,2,* Shuai Xu,3 Yuanlin Jin,1 Ren Zhang4 1Shenzhen Bao’an Traditional Chinese Medicine Hospital Group, Guangzhou University of Chinese Medicine, Shenzhen 518133, People’s Republic of China; 2The First School of Clinical Medicine, Guangzhou University of Chinese Medicine, Guangzhou 510405, People’s Republic of China; 3School of Chinese Materia Medica, Guangzhou University of Chinese Medicine, Guangzhou 510006, People’s Republic of China; 4The College of Basic Medical Science, Guangzhou University of Chinese Medicine, Guangzhou 510006, People’s Republic of China *These authors contributed equally to this work Background: Alpha lipoic acid (ALA), a type of antioxidant, is used in combination with epalrestat in the treatment of diabetic peripheral neuropathy (DPN). However, whether combined treatment is superior to epalrestat monotherapy is controversial.Methods: We conducted a systematic search of PubMed, Cochrane Library and Chinese databases to identify all randomized controlled trials (RCTs) up to October 31, 2017. Data were extracted to evaluate methodological quality and analyzed using Review Manager 5.3.0 software.Results: Twelve studies were included. Compared to epalrestat monotherapy, ALA 600 mg/d once a day (qd) combined with epalrestat 50 mg three times a day (tid) augmented the total effectiveness rate (14 days – risk ratio [RR]: 1.40, 95% CI: 1.16–1.69, P=0.0005; 28 days – RR: 1.48, 95% CI: 1.27–1.72, P<0.00001); at the same, it could improve the median motor nerve conduction velocity (MNCV) and sensory nerve conduction velocity (SNCV), peroneal MNCV, and SNCV after 14, 21, and 28 days of treatment and could reduce the Toronto Clinical Scoring System (TCSS) (weighted mean difference [WMD]: -1.60, 95% CI: (-2.91, -0.29), P=0.02) and Total Symptom Score (TSS) (WMD: -0.93, 95% CI: -1.27, -0.60, P<0.00001) after 21 days of treatment. The treatment strategy of ALA 300 mg/d qd combined with epalrestat 50 mg tid had the same effects in regard to the total effectiveness rate (RR: 1.37, 95% CI: 1.18–1.59, P<0.0001), median MNCV (WMD: 6.12, 95% CI: 5.04, 7.20, P=0.00001), median SNCV (WMD: 6.70, 95% CI: 5.75, 7.65, P=0.00001), peroneal MNCV (WMD: 6.68, 95% CI: 5.82, 7.55, P=0.00001), and peroneal SNCV (WMD: 4.27, 95% CI: 3.34, 5.20, P=0.00001) after 28 days of treatment.Conclusion: ALA combined with epalrestat is an effective option for DPN patients. Future large-sample RCTs should be conducted to further confirm this finding. Keywords: alpha lipoic acid, diabetic peripheral neuropathy, epalrestat, meta-analysis